P261 Rate of Community Acquired Pneumonia, related hospitalization, and mortality among younger unvaccinated Inflammatory Bowel Disease patients. (30th January 2023) - Khan, N; Trivedi, C; Shah, Y; Patel, M; Sundararajan, R; Xie, D; Yang, Y X
Abstract: Background: Community Acquired Pneumonia (CAP) is among the most common infections among Inflammatory Bowel Disease (IBD) patients. Current vaccine guidelines recommend vaccination at a younger age in individuals with IBD on immunosuppressive medications. Our aim was to determine the absolute and relative risk of CAP, related hospitalization, and death among unvaccinated IBD patients under the age of 65 years and compare the rates between those exposed and unexposed to immunosuppressive medications. We also sought to determine if exposure to immunosuppressive/immunomodulatory medications was associated with an increased risk of CAP in this group. Methods: We conducted a retrospective cohort study utilizing a nationwide cohort of IBD patients under the age of 65 in the Veteran Affairs Healthcare System (VAHS) who were pneumococcal vaccine naive. The unexposed group included those patients on 5-ASA medications only. Exposure was administration of any immunosuppressive medication. The primary outcome was the first occurrence of pneumonia. Secondary outcomes were pneumonia related hospitalization and mortality. We reported event rate per 1000 person-years, hazard ratio, and 95% confidence intervals (CIs) for each outcome. Results: A total of 26, 707 patients were included in our study. 513 of these patients developed pneumonia (Table 1). The overall crude incidence rate of CAP was 3.2 per 1000 patient-years (4.04/1000 patient years in the exposed vs 1.45/1000 patient-years in the unexposed). The overall crude incidence rates for pneumonia-related-hospitalization and mortality were 1.12 and 0.09 per 1000 patient-years, respectively (Table 2). In Cox regression, exposed group was associated with an increased risk of pneumonia (AHR 2.85; 95% CI 2.21 – 3.66, p < 0.001) and pneumonia-related-hospitalization (AHR 3.46; 95% CI 2.20 – 5.43, p < 0.001) (Table 3). Conclusion: Overall incidence of CAP among younger unvaccinated IBD patients was 3.2 per 1000 PY. We observed that while the incidence rates of CAP and CAP-related hospitalization were low overall, they were higher among those who received immunosuppressive therapy compared to those who only received 5-ASA medications. Knowing the exact risk of developing CAP among younger IBD patients will help patients and their physicians make informed decisions during these times of complex vaccine recommendations.